Congenital Mesenteric Defect with Transmesenteric Hernia in Children: A Case Series - Kanjiyil Thamarapilli Sreekanth; Arun Kumar Loganathan; Harshjeet Singh Bal (Wolters Kluwer Medknow Publications, 2024)
Transmesentric hernias are a type of internal hernia, in which there is herniation of bowel loops through a defect in the mesentery. They present with a wide variety of symptoms without any specific radiological features, leading to a delay in diagnosis and high mortality rate. Here, we present a case series of four patients with this rare but fatal cause of small bowel obstruction. Three children presented to the emergency department with small bowel obstruction. The other baby was a preterm neonate with an antenatal scan showing small bowel obstruction. All children underwent emergency laparotomy and were found to have a mesenteric defect with herniation and gangrene of the small bowel. Resection anastomosis of the gangrenous segment and closure of the mesenteric defect were done. The differential for small bowel obstruction in children should include transmesentric hernia. Laboratory or imaging investigations are often inconclusive. Timely exploration can save lives in this rare but life-threatening condition.